The Effect Of Family Support On Stress Level In Muhammadiyah High School 1 Malang Students With Acne Vulgaris - Febriana Nur Layli; Siska Fitriana; Dwi Nurwulan Pravitasari; Anung Putri Illahika; Dian Yuliartha lestari (Universitas Muhammadiyah Malang, 2021)
Adolescence is a stage that has relatively not reached maturity both emotionally and mentally so that in achieving good development, it is necessary to have positive support in life from the family. Stress that occurs identified as one of the triggering factors for acne vulgaris. To determine the effect of family support on stress levels in Muhammadiyah High School 1 Malang students with acne vulgaris complaints. This research an analytic observational study with a cross-sectional approach. Sampling by purposive sampling and a sample of 52 respondents. Analyzed with Spearman correlation followed by ordinal regression analysis. The results of the ordinal regression test of the effect of family support on stress levels showed a value of p = 0.000 (p<0.05), which means that there is an effect of family support on the stress level of students who have acne vulgaris complaints, with the magnitude of the OR being exp (3.323) = 27.743. The magnitude of the influence of family support in predicting the stress level of students with acne vulgaris complaints is 46.7% There is an effect of family support on stress levels in students of Muhammadiyah High School 1 Malang with acne vulgaris complaints.